(untitled) (Research, Society and Development, 2024)
Currently, equine reproduction has reproductive techniques that optimize the use of animals with selected genetic attributes, adding value and quality, avoiding possible transmission of pathogens via coitus, increasing the number of mares inseminated per stallion, and the number of descendants born per season. This study aimed to use biotechniques applied to equine reproduction with the intention of evaluating the viability of semen cooled by 36 hours from stallions of the quarter-thousand breed housed in Rolim de Moura – Rondônia. Semen from seven stallions were collected through the use of artificial vagina and live manikin, subsequently conditioned and cooled to a temperature of 5 ° C in a container refrigeration device. It was evaluated the physical characteristics, motility, vigor and concentration in four moments: 0, 12, 24 and 36 hours post-collection. Admitting the efficacy of the use of the semen cooling technique, showing that it is effective in maintaining goog motility for motility and concentration patterns (P> 0.05). However, it was able to preserve the vigor (P <0.05). It is concluded that the use of biotechnology in equine breeding maximizes the use of stallions that are housed in distant regions or that are limited to transport between regions.